2021
DOI: 10.14738/assrj.85.10161
|View full text |Cite
|
Sign up to set email alerts
|

effects of COVID-19 Pandemic on the Psyche and Productivity of Pharmaceutical Sales Workforce in an African Country; A descriptive case study

Abstract: Pharmaceutical sales representatives are a pivotal workforce in the healthcare system. Due to the global impact of COVID-19, the impact on the psyche and morale of the pharmaceutical sales workforce has to be examined. The primary objective of the study was to assess the possible impact of the COVID-19 pandemic on the psyche and productivity of the pharmaceutical sales workforce in Nigeria. A questionnaire-guided cross-sectional survey was used to collect data from pharmaceutical sales personnel across the six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In order to safeguard medicine supply in future, immediate attention to sales workforce welfare is required. 3…”
Section: Introductionmentioning
confidence: 99%
“…In order to safeguard medicine supply in future, immediate attention to sales workforce welfare is required. 3…”
Section: Introductionmentioning
confidence: 99%
“…The rapid shift to more technology-based operations is partly adduced to the changes in operations of pharmaceutical executives due to the challenges of the COVID-19 pandemic and limited resources due to global economic downturn (Oamen, 2021;Kwak and Chang, 2016;Kwak and Chang, 2022;Kim and Chang, 2022). Hence, optimizing client engagement and business profitability has led to a paradigm shift from face-to-face or physical contact to more emphasis on the remote and virtual interactions (Molloy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…CFA therefore confirms the construct validity of the instrument(s) in relation to the researchers' culture because if the instrument is not measuring something meaningful, the consequent analyses may be meaningless or even misleading [Cheung, 2009]. Previous studies have examined the various work roles and responsibilities of pharmaceutical sales executives to include drug information services to health care, medication supply to retailers, customer care services, community enlightenment, and direct selling [Ugbam & Okoro, 2017;Oamen, 2021a;Oamen, 2021b]. However, to the best of the researchers' knowledge, there has not been a study that specifically confirmed the work attributes of pharmaceutical sales representatives during COVID-19 especially in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the global challenge presented by the COVID-19, the work attributes and occupational structures have largely adapted to accommodate the adverse effects of the COVID-19 on the work-life characteristics of sales professionals in the pharmaceutical industry. Several studies have shown that there have been effects on both work life and the characteristics of job roles [Elbeddini & Yeats, 2020;Bashir et al, 2021;Oamen, 2021a;Oamen, 2021b]. Hence, there is a need to investigate the explored factors in a previous study by Oamen [Oamen, 2021c] to confirm the validity of the structural model using CFA.…”
Section: Introductionmentioning
confidence: 99%